2003
DOI: 10.1523/jneurosci.23-17-06740.2003
|View full text |Cite
|
Sign up to set email alerts
|

β-Amyloid Regulation of Presynaptic Nicotinic Receptors in Rat Hippocampus and Neocortex

Abstract: Alteration by beta-amyloid (Abeta) of signaling via nicotinic acetylcholine receptors (nAChRs) has been implicated in the early stages of Alzheimer's disease. nAChRs function both post- and presynaptically in the nervous system; however, little is known about the functional consequence of the interaction of Abeta with these receptors, particularly those on presynaptic nerve terminals. In view of the strong correlation between loss of synaptic terminals and dementia, together with the reduction in nAChRs in Alz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
165
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 187 publications
(186 citation statements)
references
References 57 publications
21
165
0
Order By: Relevance
“…Moreover, lipid interaction with the M4 transmembrane domain of the nAChR regulates its channel kinetics (39), and an interaction between A␤ and the lipid microenvironment around the nAChR may, in turn, regulate the receptor. We therefore first constructed a chimeric receptor containing the ECD from the ␣7-nAChR and the transmembrane and intracellular domains from the 5-HT 3 receptor (13, 37, 38), a ligand-gated ion channel that is very closely related to nicotinic receptors but not activated by A␤ (13,16,21). The results using the chimeric receptor (␣7 V202-5HT3A ) showed that the ECD of the ␣7-nAChR mediates activation of the receptor by A␤.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, lipid interaction with the M4 transmembrane domain of the nAChR regulates its channel kinetics (39), and an interaction between A␤ and the lipid microenvironment around the nAChR may, in turn, regulate the receptor. We therefore first constructed a chimeric receptor containing the ECD from the ␣7-nAChR and the transmembrane and intracellular domains from the 5-HT 3 receptor (13, 37, 38), a ligand-gated ion channel that is very closely related to nicotinic receptors but not activated by A␤ (13,16,21). The results using the chimeric receptor (␣7 V202-5HT3A ) showed that the ECD of the ␣7-nAChR mediates activation of the receptor by A␤.…”
Section: Discussionmentioning
confidence: 99%
“…To do so, we constructed a chimeric receptor by fusing the nAChR ECD together with the transmembrane and intracellular domains of the 5-HT 3 serotonin receptor (13,37,38), as the binding site in ␣7-nAChR for classical nicotinic agonists is located in the ECD, but A␤ may also influence ␣7-nAChR activity through an additional interaction with the plasma membrane (23), perhaps via lipid-interacting residues in the transmembrane domains (39). Moreover, it was shown previously that the 5-HT 3 receptor is unaffected by A␤ (13,16,21). The chimeric receptor is denoted by ␣7 V202-5HT3A , as valine (V) at position 202 of mouse ␣7-nAChR lies at the border between the extracellular and first transmembrane domain of the ␣7-nAChR (38).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of a7 n-AChR proteins have been shown to be decreased in the brain of AD patients, a pathology characterized by severe memory impairments (Nordberg, 2001). In addition, a direct interaction of the b-amyloid peptide with a7 n-AChRs has also been described at native and recombinant rat a7 n-AChRs, leading to functional alteration of these receptors (Dineley et al, 2002;Grassi et al, 2003;Dougherty et al, 2003;Nordberg, 2001). It has been hypothesized that the attention and cognitive symptoms that are characteristic of schizophrenia and AD may involve a degeneration or a hypofunction of the cholinergic inputs, originating from the septum to the hippocampus (Grassi et al, 2003;Gray et al, 1996;Freedman et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The regulation of neurotransmitter release by presynaptic nAChRs is also Ca 2+ -dependent, involving Ca 2+ influx via the nAChR ion pore and/or voltage-gated ion channels (VGCCs) activated by nAChR-mediated depolarization [10]. Direct measurement of presynaptic [Ca 2+ ] i in individual brain nerve terminals, coupled with pharmacological assessment, has demonstrated substantial and relatively sustained Ca 2+ increases to acute application of nicotine, the nature of which depends upon the specific brain region [11][12][13]. The sustained nicotine-induced presynaptic Ca 2+ responses are consistent with the sustained nicotine-induced increases in spontaneous excitatory release observed in a variety of preparations [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%